Oil palm cultivation in India: past, present and future scenario: OIL PALM CULTIVATION IN INDIA: PAST, PRESENT AND FUTURE SCENARIO - P KALIDAS,; S CHANDER RAO,; K J PRABHAKAR RAO, (Journal of Oilseeds Research, 2014)
Cultivation of oil palm, Elaeis guineensis Jacq. by giving irrigation is a unique practice in the world and is being followed only in India. The palms that were brought for ornamental purpose later paved the way to utilize them as source of vegetable oil. The wide gap between demand and supply in vegetable oil production using the nine annual oilseed crops, the population explosion, the increased consumption of vegetable oil due to increased GDP forced to grow the crop under Indian conditions to obtain more yield. The role played by various organizations in the development of oil palm industry is worth mentioning without which it would not have been successful. The roleplayed by AICRP on Palms (ICAR) in raising the demonstration plots to find the feasibility of the crop in different areas of the country, DAC by appointing three committees to identify the potential areas for cultivation, DBT for taking up of large scale demonstrations and initiation of mutation breeding using gamma rays irradiation of seed sprouts, UNDP by sanctioning two mega projects on training and seed production and finally the TMOP taking the overall control of the project and maintain it successfully to achieve the best results are worth mentioning. The Government policies, are however, need to be reviewed at frequent intervals as these are responsible for the setbackthat were observed in different periods. If these are taken care off, the oil palm industry will be a successful venture in the country.